Dyadic effects of perceived burden and psychological distress on quality of life among Chinese advanced cancer patients and their caregivers - Panpan Cui; Jiansai Ai; Xinyi Chen; Chunyan Cheng; Jiaoxia Shi; Shifeng Li; Ming Yang; Changying Chen; Hengyu Hu (Scientific Reports)
Abstract This study aims to explore the mediating role of psychological distress in the association between perceived burden and quality of life (QoL) in advanced cancer patient-caregiver dyads. 241 dyads in five tertiary hospitals in a province were investigated by using the Edmonton Symptom Assessment System, Zarit Burden Interview, the Patient Health Questionnaire-4, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 15 Palliative scores, and the Short Form Health Survey 8. The actor-partner interdependence mediation model (APIMeM), which assesses both individual (actor) and interdependent (partner) effects within dyadic relationships, was employed to analyze how burden and psychological distress interact across dyad members. Analysis was conducted using Mplus v8.0. Regarding the actor effects, the mediating role of psychological distress between perceived burden and QoL was confirmed in advanced cancer patients (B = −0.223, p = 0.001) and their caregivers (B = −0.168, p < 0.001). Regarding the partner effects, there were no significant correlations between caregiver burden and patients’ psychological distress (B = 0.015, p = 0.199), patients’ QoL (B = 0.113, p = 0.278), or the indirect association of caregiver burden with patients’ QoL through psychological distress (B = −0.034, p = 0.259). However, caregivers’ psychological distress was positively correlated with patients’ symptom burden and mediated the association between patients’ symptom burden and caregivers’ QoL (B = −0.090, p = 0.001). The study highlights the importance of taking a dyadic perspective in the context of advanced cancer. Dyadic interventions targeting their perceived burden and psychological distress may be beneficial to their QoL.